Predicting Sexual Intention to Engage In Premarital Sex among Late Adolescent in Kuantan Government Secondary Schools: An Application Of The Theory Of Planned Behavior - Abdullah, Faiza; Draman, Samsul; Abd Aziz, Karimah Hanim; Zainuddin, Nurul Akmanidar; Muhammad, Noor Azimah (IIUM Medical Journal Malaysia, 2018)
Introduction: The Theory of Planned Behavior (TPB) states that behaviour is determined by four main domains of social-cognitive factors; attitudes, social norms, self-efficacy and sexual intention. The aim of this study was to explore the correlation of the socio-cognitive factors predicting sexual intention to engage in premarital sex amongst late adolescent in Kuantan government secondary schools. Materials and Methods: This cross-sectional study was conducted among 466 single students aged 18 to 19 years in nine government secondary schools in Kuantan district. A self-administered validated Youth Sexual Intention Questionnaire (YSI-Q) that measured permissive attitude, perception of social norms, perceived selfefficacy and sexual intention towards premarital sex activity has been used. Statistical analyses were done using IBM SPSS version 22.0. Results: There was a significant difference of sexual intention between male (35.6%) and female (64.4%) students with a mean(SD) of 10.54(3.8) and 7.3(2.9) respectively. Permissive attitude, perception of social norms (peer pressure) and perceived self-efficacy have significant positive correlation on sexual intention towards premarital sex with the value of (r=0.579, p<0.001), (r=0.513, p<0.001) and (r=0.253, p<0.001) respectively. Thus, the higher permissive attitude, social norms and perceived self-efficacy led to higher sexual intention. In addition, a student with premarital sex experience (1.5%) has significant higher sexual intention than student without premarital sex experience given by mean(SD); 14.43(2.5) vs. 8.25(3.6). Conclusion: The Theory of Planned Behavior has a positive correlation towards premarital sex among late adolescent. It might successfully guide the development of sexual abstinence intervention-based theory to reduce unsafe sexual behavior among adolescents.